Els derivats d’«esse» i «stare» en les llengües romàniques - Ramos, Joan Rafael (Caplletra. Revista Internacional de Filologia, 2001)
This paper presenta a contrastive analysis of the Romance verbs derived from ESSE and STARE. The lexical and syntactic characteristics of these verbs in Latin and their locative and atributive uses clearly contrast with actual Romance uses. This contrast highlights the variable extension of the verbs derived from STARE assuming the space of those derived from ESSE.One extreme of the clyne is represented by the Hispanic languages (i.e., Spanish, Portuguese and Catalan), which have developed more uses and thus extended further the STARE forms. On the opposite extreme, there is French, which has no STARE uses. In between, there are Occitan, Sardinian, Italian and Romanian, which include some forms derived from STARE, but their extension is inferior to the extension reached in the Hispanic languages. The analysis focusses on the factors that have interacted and influenced on this extension of use and points to the present tendencies.